Williams Syndrome and Agreement: The Case for Spanish Speakers - Antònia Llull Febrer; Lluís Barceló-Coblijn; Elga Cremades (Languages)
This paper examines morphosyntactic agreement in gender and number within the spontaneous spoken discourse of Spanish-speaking adults with Williams syndrome (WS), compared to that of typically developing (TD) speakers. Data were collected through natural speech transcriptions from both WS and TD groups. The analysis was conducted using Netlang 1.0.0—a piece of corpus annotation software—based on Dependency Grammar, to capture agreement patterns among determiners, nouns, and adjectives. The findings reveal that WS speakers’ gender and number agreement patterns are closely aligned with those observed in TD speakers, with only minor variations, such as a slight tendency toward unmarked gender forms among TD participants. Additionally, error rates are low in both groups, suggesting that observed discrepancies might be due to individual variation rather than condition-specific deficits, even though the statistical power of the study is limited. These results contribute to the ongoing debate on language abilities in WS, indicating that individuals with WS produce morphosyntactic agreement similarly to individuals with TD. Further research with larger datasets is recommended to validate these results, as individual variability within the WS group underscores the need for a more nuanced approach to analysis.